Biological activity of plant extracts on the small tomato borer Neoleucinodes elegantalis, an important pest in the Neotropical region - Fragoso, Débora F.M.; Túler, Amanda C.; Pratissoli, Dirceu; Carvalho, José Romário; Valbon, Wilson R.; Queiroz, Vagner T. de; Pinheiro, Patrícia F.; Costa, Adilson V.; Bueno, Regiane C.O.F. [UNESP] (Elsevier, 2021)
The small tomato borer Neoleucinodes elegantalis (Guenée) (Lepidoptera: Crambidae), is the most harmful tomato pest in the Neotropical region. Control of this insect is a complex task that relies heavily on the use of chemical products and the correct timing to target the initial developmental stages (eggs and larvae) before they penetrate the tomato fruits. Given the potential of plant-derived compounds for controlling pests, the first step of this study was to assess the insecticide activity of the aqueous extracts of Capsicum annuum L. (bell pepper), Allium sativum L. (garlic), Nicotiana tabacum L. (commercial rope tobacco), and the crude oil of Ricinus communis L. (castor bean) against N. elegantalis larvae. Here, it was reported that the commercial rope tobacco extract was promising against N. elegantalis larvae (up to 100% control), and the extracts of C. annuum, A. sativum, and R. communis presented very low insecticide activity (< 50% mortality). The rope tobacco extract was then selected to assess its effectiveness not only on eggs and the prepupal stage, but also on female oviposition behavior. Finally, the components of rope tobacco were assessed through phytochemical analysis. Our toxicological bioassays revealed ovicidal (LC50 = 2.69 g/L) and larvicidal (LC50 = 1.64 g/L) activity of tobacco extract. Furthermore, exposure to low tobacco extract concentrations (0.2 g/L) caused significantly decreased survival abilities of the prepupal stage, similar to indoxacarb insecticide (positive control). Tomato fruits previously treated with low concentrations (0.2 and 3.1 g/L) reduced the egg-laying performance of N. elegantalis in short-and long-term exposure. Chemical analysis of the tobacco rope extract revealed not only nicotine as the major component, but also the presence of phenolics, terpenoids, steroids, and other alkaloids. Collectively, our findings indicate that aqueous extract of rope tobacco shows biological activities in different developmental stages, including deterrent effects on N. elegantalis oviposition, which may position it as a promising tool to prevent pest attacks on tomato fruits.
Keywords: Bioinsecticide; Egg-laying performance; Nicotiana tabacum; Ovicidal activity; Solanaceae pest